Sustainable Finance: Nurturing Your Savings and the Planet - Eko Tama Putra Saratian; Imma Rokhmatul Aysa; Urip Sudiana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study investigates the dynamics of sustainable finance practices, environmental awareness, and financial outcomes among customers of Bank Artha Graha. Through quantitative analysis employing structural equation modeling, the research examines the direct and indirect effects of Sustainable Financial Practices and Environmental Awareness on Sustainable Investment Returns and Savings Growth. Findings reveal a significant direct influence of Sustainable Financial Practices on both Sustainable Investment Returns and Savings Growth, emphasizing the importance of integrating environmental, social, and governance criteria into financial products and services. While Environmental Awareness demonstrates a marginal direct effect on Savings Growth, it does not significantly impact Sustainable Investment Returns. However, the analysis indicates that Sustainable Financial Practices indirectly influence Savings Growth through their impact on Sustainable Investment Returns. These results underscore the critical role of sustainable finance principles in promoting financial growth aligned with environmental responsibility, offering valuable insights for stakeholders in the banking industry and beyond.